2018
DOI: 10.1080/13813455.2018.1437186
|View full text |Cite
|
Sign up to set email alerts
|

Protective and anti-inflammatory effects of hydroalcoholic leaf extract of Origanum vulgare on oxidative stress, TNF-α gene expression and liver histological changes in paraquat-induced hepatotoxicity in rats

Abstract: O. vulgare leaf extract has inhibitory effects on paraquat-induced liver damage due to its antioxidant properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 34 publications
4
23
0
Order By: Relevance
“…Our results are in agreement with these reports and we have demonstrated that HYP is associated with enhanced oxidative stress and hepatotoxicity. Therapeutic interventions of natural origin which are capable of attenuating oxidative stress are known to exert hepatoprotective and other beneficial effects [22][23][24]. Our findings are in line with these reports and we demonstrated that hydroalcoholic extract of S. chirata possesses strong antioxidant potential as indicated by the reduced ROS generation, improved catalase activity, enhanced GSH levels, and inhibition of lipid peroxidation (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Our results are in agreement with these reports and we have demonstrated that HYP is associated with enhanced oxidative stress and hepatotoxicity. Therapeutic interventions of natural origin which are capable of attenuating oxidative stress are known to exert hepatoprotective and other beneficial effects [22][23][24]. Our findings are in line with these reports and we demonstrated that hydroalcoholic extract of S. chirata possesses strong antioxidant potential as indicated by the reduced ROS generation, improved catalase activity, enhanced GSH levels, and inhibition of lipid peroxidation (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…In treated rats with NAC and silymarin, however, the serum levels of GOT and GPT decreased compared with the second group (Table 2). Previous studies had shown that antioxidants can keep integrity of cell membrane and decrease exudation of enzymes through free radical scavenging activities (Giridharan & Sabina, 2017;Sharifi-Rigi et al, 2019). Therefore, the Furthermore, DIC has been reported to decline the activity of antioxidant enzymes such as SOD and CAT (Giridharan & Sabina, 2017;Nouri, Heidarian, & Nikoukar, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In treated rats with NAC and silymarin, however, the serum levels of GOT and GPT decreased compared with the second group (Table ). Previous studies had shown that antioxidants can keep integrity of cell membrane and decrease exudation of enzymes through free radical scavenging activities (Giridharan & Sabina, ; Sharifi‐Rigi et al, ). Therefore, the reduction of serum GPT and GOT activities, at least in part, may be resulted from the antioxidant activity of NAC on the cell membrane in DIC‐toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations